2012
DOI: 10.1163/156854112x638415
|View full text |Cite
|
Sign up to set email alerts
|

Loop-mediated isothermal amplification for rapid and precise detection of the burrowing nematode, Radopholus similis, directly from diseased plant tissues

Abstract: A novel, simple, rapid and highly sensitive assay and diagnostic tool for the burrowing nematode, Radopholus similis, was developed using a loop-mediated isothermal amplification (LAMP). The LAMP assay was targeted on the specific fragments of rRNA gene D2-D3 regions of R. similis. The detection limitation of the LAMP assay was as low as ten copies of plasmid DNA containing the target DNA, 10 fg of genomic DNA and 5 × 10−5 nematodes. The detection sensitivity of the LAMP method for R. similis DNA was 10-100 ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 22 publications
0
18
0
3
Order By: Relevance
“…Previous results found that the sensitivity of the LAMP assay was higher than conventional PCR9262728. In the present study, the detection limit was low to 1/200 000 nematode DNA, whereas the conventional PCR approach usually requires a single nematode, Williamson et al 11.…”
Section: Discussionmentioning
confidence: 42%
See 4 more Smart Citations
“…Previous results found that the sensitivity of the LAMP assay was higher than conventional PCR9262728. In the present study, the detection limit was low to 1/200 000 nematode DNA, whereas the conventional PCR approach usually requires a single nematode, Williamson et al 11.…”
Section: Discussionmentioning
confidence: 42%
“…Traditional M. hapla detection assays based on PCR methods1112131530 are time-consuming and require sophisticated equipments as well as expertise. LAMP is a novel, simple, rapid and precise amplification method that can be adapted for diagnosing plant-parasitic nematodes, as previously reported925262728. In this study, we designed a set of five specific LAMP primers to detect M. hapla .…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations